ChemInform Abstract: Recent Progress Toward the Introduction of Functionalized Difluoromethylated Building Blocks onto C(sp2) and C(sp) Centers. Issue 45 (November 2015) - Belhomme, Marie‐Charlotte; Besset, Tatiana; Poisson, Thomas; Pannecoucke, Xavier
Abstract Review: [86 refs.